Chapter 3 Foreign mining corporations on trial - Radley, Ben (Oxford University Press, 2024)
By the 2010s, the view that state mismanagement and inefficiencies underlay the Congo's economic malaise had become so commonplace as to permeate nearly all thinking about development in the country. The aim of this chapter is to challenge this line of thinking and question the Consensus wisdom of moving from domestic-owned to foreign-owned industrial mining based on a belief in the superior efficiency of the latter. By charting the rise and fall of Belgian-owned SOMINKI (1976-1997) and Canadian-owned Banro (1995-2019) in eastern Congo, its main line of argument is that foreign-owned and managed mining corporations are no less vulnerable to mismanagement, firm inefficiencies, and volatile prices than their state-owned counterparts. This included, in the case of Banro, rent-seeking behaviour, redirecting value to overseas directors and shareholders at the expense of productive capacity and to the detriment of the Congolese state and Congolese firms and labour.